Socialization of Bridge Base Online - Topo Yono; Agung Dwi Darmawan; Arya T Candra; Ratna Mustika Yasi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Bridge sport game, in playing the player must go through the process of playing mini bridge first. You have to master how to play, you have to know the High Card Point (HCP), the names of the cards, the bidding sheet, the score sheet, this is the basis for playing bridge. Bridge base online is a way of learning bridge online. This online bridge base is learning that must be applied by teachers or trainers in schools that are in a formal school education environment to apply online training to simplify and shorten how to play bridge can be done independently without involving other people. In conventional games, at least 4 people are required to play bridge. With bridge base online everything can be done alone without involving many people and done anytime and anywhere as long as there is an internet connection